2021
DOI: 10.1016/j.paid.2020.110397
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic practice: Horror fans and morbidly curious individuals are more psychologically resilient during the COVID-19 pandemic

Abstract: One explanation for why people engage in frightening fictional experiences is that these experiences can act as simulations of actual experiences from which individuals can gather information and model possible worlds. Conducted during the COVID-19 pandemic, this study (n = 310) tested whether past and current engagement with thematically relevant media fictions, including horror and pandemic films, was associated with greater preparedness for and psychological resilience toward the pandemic. Since morbid curi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 25 publications
3
60
1
3
Order By: Relevance
“…This element emerges also among those participants, like Veronica, Giorgio and Gianluca, who explicitly reported to have actively chosen a movie or a TV series in which there was a protagonist they knew they could identify with. This process, namely the need to identify with a fictional character and the consequent feeling of hope and faith in the future that came with it, caused a cathartic liberation, very similar to the one already described by ancient Greek philosophers and tragedians Plato, Aristotle, Aristophanes (40), and which has been already documented in scientific literature as a possible beneficial effect of cinema, especially in this current time of global pandemics (41,42). Finally, there were also participants who, despite not having any initial intention to watch virusrelated movie or TV series, found them by chance and eventually could not but being absorbed in because of the inevitable resemblance with their reality.…”
Section: Discussionmentioning
confidence: 70%
“…This element emerges also among those participants, like Veronica, Giorgio and Gianluca, who explicitly reported to have actively chosen a movie or a TV series in which there was a protagonist they knew they could identify with. This process, namely the need to identify with a fictional character and the consequent feeling of hope and faith in the future that came with it, caused a cathartic liberation, very similar to the one already described by ancient Greek philosophers and tragedians Plato, Aristotle, Aristophanes (40), and which has been already documented in scientific literature as a possible beneficial effect of cinema, especially in this current time of global pandemics (41,42). Finally, there were also participants who, despite not having any initial intention to watch virusrelated movie or TV series, found them by chance and eventually could not but being absorbed in because of the inevitable resemblance with their reality.…”
Section: Discussionmentioning
confidence: 70%
“…In the cognitive playground of a fictional world, people can learn what a particular situation looks like and engage in emotional and behavioral strategies that could prepare for related situations in the real world (Morin et al, 2019;Scalise-Sugiyama, 2001). Supporting this hypothesis, Scrivner et al (2021) found that horror fans experienced less psychological distress during the COVID-19 pandemic than non-horror fans. Specifically, horror fans reported less anxiety, depression, irritability, and sleeplessness in the early months of the pandemic.…”
Section: How Horror Could Lead Tomentioning
confidence: 71%
“…By watching movies that simulated the world during or after a catastrophic event, viewers can gather information about what the world looks like and how people might behave during catastrophic events. In turn, this may lead to a feeling of preparedness and resilience in the face of fearful situations in the real world (Scrivner et al, 2021).…”
Section: Personality and Horrormentioning
confidence: 99%
“…The perhaps surprising answer is: Fans of horror films and "prepper" genres (e.g., alieninvasion, apocalyptic, and zombie films). Scrivner et al (2020) found that past and current engagement with such fiction was associated with greater preparedness and psychological resilience in the COVID-19 pandemic. This preparedness constituted feeling mentally prepared, not being surprised, previously having imagined it may happen, being able to predict the course of events of the pandemic, and even knowing what items to buy 1 .…”
Section: Planning and Future Thoughtmentioning
confidence: 95%
“…This study supports the idea that we use simulations, including those offered by fiction, to prepare for real-world events, and offers empirical support for the hypothesis that fiction may serve adaptive functions (Carroll, 2004;Clasen, 2019). The undead in a zombie movie may be implausible, but the interpersonal and societal upheavals depicted may still allow people to glean information about ecological, social, and psychological consequences of societal turmoil and collapse, and about the qualities of existence under a state of emergency (Scrivner et al, 2020). The afforded information may be novel: The realistic pandemic movie Contagion (2011), depicting a global outbreak of a respiratory virus, soared to the top of streaming lists at the beginning of the COVID-19 pandemic, suggesting that people may look to fictional representations to understand and process situations that to them are unprecedented (Reis Filho, 2020;Scrivner, 2021a).…”
Section: Planning and Future Thoughtmentioning
confidence: 99%